Visual sensory and perceptive functioning in 5‐year‐old very preterm/very‐low‐birthweight children. (3rd March 2014) - Geldof, Christiaan JA; Oosterlaan, Jaap; Vuijk, Pieter Jelle; de Vries, Meindert J; Kok, Joke H; van Wassenaer‐Leemhuis, Aleid G
<x xml:space="preserve">Abstract</x> Aim To examine visual sensory and perceptive functions, study their interrelations, and explore associations between visual dysfunctions and intelligence in very preterm/very‐low‐birthweight (VP/VLBW) children. Method One‐hundred and sixteen VP/VLBW children (57 males, 59 females; mean gestational age 30.1wks, SD 2.3; mean corrected age 5y 6mo, SD 1mo) and 73 term‐born children (40 males, 33 females; mean gestational age 39.9wks, SD 1.3; mean age 5y 6mo, SD 3mo) completed visual sensory (acuity, visual field, contrast‐, color‐, and stereovision), perceptive (visual coherence, and Developmental Test of Visual Perception non‐motor scale), and intelligence assessments. Results Compared with term‐born children, VP/VLBW children had reduced acuity (d=0.70, p<0.001), inferior visual field (d=0.67, p<0.001), and stereovision (v=0.19, p=0.008). VP/VBLW children showed weaker static coherence (d=0.49, p=0.001) and Position in Space (d=0.41, p=0.006) performance, independent of visual sensory deficits, and showed lower Verbal IQ (VIQ) and Performance IQ (PIQ; p<0.001). Visual perceptive functioning accounted for 13% of variance in VIQ, and for 35% of variance in PIQ. Interpretation Visual sensory and perceptive dysfunctions are present in VP/VLBW children and occur largely independently of each other. Visual perceptive dysfunctions are moderately associated with PIQ, and weakly with VIQ.